Design and manufacture of a 10-tonne hydraulic press - Amiolemhen , Patrick-Ejebheare; Nosa, Andrew (Journal of Production Engineering, 2019)
The design and construction of a 10-ton hydraulic press for laboratories use in most of our higher institutions using locally sourced materials was carried out. Frames and cylinders are the main components of the hydraulic press. An existing design was examined and the basic features and components were identified after which a market survey was conducted to access the availability or otherwise of the components. The major components of the press designed include the cylinder and piston arrangement, the frame and the hydraulic circuit. The machine was then designed and produced according to specification and was subsequently calibrated and tested. The principal parameters of the design included the maximum load 10 tonnes, the distance the load resistance has to move, the system pressure, the cylinder area and the volume flow rate of the working fluid.